Impact of parents' technology use on 18- to 24-month-old infants' adaptive behaviors. (June 2019) - Atlı, Sibel; Gunuc, Selim; Kuss, Daria; Baran, Gülen
The aim of this study is to investigate the relationship between adaptive behaviors of 18- to 24-month-old infants and their parents' use of technology. For this purpose, a survey research method was used. The sample consisted of 116 people who are 58 volunteering married couples with 18- to 24-month-old infants and were registered in family health centers in Turkey's Eastern Anatolia Region. Comparison analyses were conducted between parents' demographic variables (i.e., education background) and their use of technology (i.e., Internet, smartphone) and adaptive behaviors of their 18- to 24-month-old infants. Adaptive behaviors of infants were measured with ABAS-3 (Adaptive Behavior Assessment System, Third Edition) and the profiles of parents using technology were measured with a survey developed by the researchers. The results showed that parents' use of technology had an impact on adaptive behaviors of 18- to 24-month-old infants. Infants of mothers who did not engage in any Internet activity have higher adaptive behavior scores. The infants of mothers who engaged in activities such as games, videos, and music on the Internet together with their 18- to 24-month-old infants had low scores on adaptive behaviors in terms of concept, self-management, leisure, and communication. According to the findings, various suggestions are presented for parents, researchers, and practitioners.